Application of CO2 miscible flooding in ultra-low permeability beach-bar sand reservoir - Yang, Sen; Xu, Yangmengzhe; Huang, Zhiwei; Zhang, Qunshuang; Liu, Ting; Li, Xuelei (Frontiers in Earth Science, 2022)
The beach-bar sand reservoir of the Sha 4 Member of the Shahejie Formation in the Dongying Sag is the main oil-bearing formation in this area. In recent years, its proven reserves have been getting lower and lower, and the poor petrophysical properties of the reservoir have made water injection development difficult. In turn, it results in a rapid decline in elastic development productivity and low oil recovery. In this study, the experimental evaluation and numerical simulation research on the adaptability of CO2 flooding in beach-bar sand reservoirs are carried out on the basis of fully investigating the successful examples of CO2 flooding conducted by the previous. According to the geological characteristics of the reservoir in the CL area of Dongying Sag, reasonable reservoir engineering parameters and surface injection procedures for CO2 flooding have been formulated. Experiments show that after the completion of water flooding, the recovery factor of CO2 continuous flooding is 85.64%. It proves that the recovery factor of CO2 flooding is higher than that of water flooding. Field tests have shown that CO2 molecules in beach-bar sand reservoirs behave in a supercritical state underground, which is easier to inject into the reservoir than water. In addition, the displacement distance of CO2 is obviously larger than that of water injection development. The gas-oil ratio variation of different flooding types is different, and CO2 flooding can effectively increase the formation energy, and improve the oil recovery and economic benefits of this type of reservoir.